2020
DOI: 10.3390/biomimetics5040061
|View full text |Cite
|
Sign up to set email alerts
|

Improved Weathering Performance of Poly(Lactic Acid) through Carbon Nanotubes Addition: Thermal, Microstructural, and Nanomechanical Analyses

Abstract: To understand the interrelationship between the microstructure and degradation behavior of poly(lactic acid) (PLA), single-walled carbon nanotubes (CNTs) were introduced into PLA as nucleating agents. The degradation behavior of PLA-CNT nanocomposites was examined under accelerated weathering conditions with exposure to UV light, heat, and moisture. The degradation mechanism proceeded via the Norrish type II mechanism of carbonyl polyester. Differential scanning calorimetry (DSC) studies showed an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…12 Extensive research has been done for improving as well as tuning the physical and mechanical properties of PLA, which usually involves the addition of nanoparticles or blending with another polymer. [13][14][15][16][17][18] In a research conducted by Kim et al, they found that upon adding a small amount of carbon nanotubes/graphene oxide hybrid nanoparticle system, the permeability of oxygen into PLA film would be greatly reduced. 5 Urquijo et al observed that the percentage of gas penetration into a blend of PLA and poly (ε-caprolactone) could significantly be reduced by adding an appropriate amount of nanoclay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Extensive research has been done for improving as well as tuning the physical and mechanical properties of PLA, which usually involves the addition of nanoparticles or blending with another polymer. [13][14][15][16][17][18] In a research conducted by Kim et al, they found that upon adding a small amount of carbon nanotubes/graphene oxide hybrid nanoparticle system, the permeability of oxygen into PLA film would be greatly reduced. 5 Urquijo et al observed that the percentage of gas penetration into a blend of PLA and poly (ε-caprolactone) could significantly be reduced by adding an appropriate amount of nanoclay.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been done for improving as well as tuning the physical and mechanical properties of PLA, which usually involves the addition of nanoparticles or blending with another polymer 13–18 . In a research conducted by Kim et al, they found that upon adding a small amount of carbon nanotubes/graphene oxide hybrid nanoparticle system, the permeability of oxygen into PLA film would be greatly reduced 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its biodegradable nature, PLA undergoes degradation under the influence of environmental factors, leading to a significant decline in its performance, thereby failing to meet usage requirements. 8,9 PLA is susceptible to aging degradation when exposed to conditions such as light during the usage process, 4,10 undergoing photodegradation from the surface to the interior upon direct irradiation. Under light excitation conditions, the carbonyl and hydroxyl groups in PLA molecules react with oxygen, forming intermediate ions and generating a large number of free radicals, gradually breaking down the PLA molecules into small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Depan et al demonstrated that carbon nanotubes could act as nucleating agents to increase the nucleation density and form smaller spherulites. The poly­(lactic acid) and carbon nanotube composite changed the microstructure and improved the crystallinity compared with pure poly­(lactic acid), resulting in better stability against weathering . Koumoulos et al showed that carbon fibers added into poly­(methacrylic acid) (PMAA) reinforced the interphasial properties.…”
Section: Introductionmentioning
confidence: 99%
“…The poly(lactic acid) and carbon nanotube composite changed the microstructure and improved the crystallinity compared with pure poly(lactic acid), resulting in better stability against weathering. 10 Koumoulos et al showed that carbon fibers added into poly(methacrylic acid) (PMAA) reinforced the interphasial properties. The modified PMAA had the unique molecular weight of grafted macromolecules and different chain-length brushlike structures, which enabled the composite to maintain better mechanical properties after weathering.…”
Section: Introductionmentioning
confidence: 99%